Really and truly - Rivard, Émilie, 1982- (Owlkid Books, 2011)
Charlie is very close to his grandfather, who loves to tell fanciful stories about pirates, witches, and gnomes that amuse Charlie to no end. But lately, Charlie's grandpa doesn't have any new stories to tell. In fact, some days grandpa doesn't even recognize Charlie. A disease has stolen grandpa's memories, his appetite, and even his smile. Charlie wants so much to make his grandpa smile again that he comes up with a plan to tell him stories. The same ones that grandpa used to tell Charlie to make him laugh! Without shying away from the inevitable heartache that comes from watching loved ones suffer, Really and Truly is a spirited book for young readers struggling to remain optimistic during troubling times.